Tinplate and tin can quality - Salcedo, Maria Rosario C.; Acevedeo, Teresita P. (1977)
Based on the porosity test, there is no significant difference among the samples of primes and seconds tinplate. This does not necessarily indicate, however, that prime and seconds have the same corrosion resistance. The tin coating weight of Carnation samples are within the minimum test values of tinplate and tin coating weight standards. Those of second or third class samples have variable tin coating weights. To the tin can manufacturer the more important quality attributes of cans are base weight, tin coating weight, temper and seam dimensions. Each of these play an important role in the performance of the can. The more important quality attributes of a can a food manufacturer should consider are base weight, tin coating weight, the steel base and seam dimensions. 70 to 90 pounds per base box is the base weight range for food products. Tin coating weight of 0.50 to 0.75 pound per base box is generally used for food products. The type of steel base of local tin plate is MR which is not suitable for highly corrosive foods. The solder and general appearance are also important features to consider.
Appendices: leaves 42-57.
Thesis (B.S.)--University of the Philippines, Quezon City.
Typescript.
Keywords: Tin plate -- Testing; Food containers; Tin cans